Calculations of nonlinear response properties using the intermediate state representation and the algebraic-diagrammatic construction polarization propagator approach: two-photon absorption spectra - Knippenberg, Stefan; Rehn, Dirk R.; Wormit, Michael; Dreuw, Andreas (The journal of chemical physics, 2012)
An earlier proposed approach to molecular response functions based on the intermediate state representation (ISR) of polarization propagator and algebraic-diagrammatic construction (ADC) approximations is for the first time employed for calculations of nonlinear response properties. The two-photon absorption (TPA) spectra are considered. The hierarchy of the first- and second-order ADC/ISR computational schemes, ADC(1), ADC(2), ADC(2)-x, and ADC(3/2), is tested in applications to H2O, HF, and C2H4 (ethylene). The calculated TPA spectra are compared with the results of coupled cluster (CC) models and time-dependent density-functional theory (TDDFT) calculations, using the results of the CC3 model as benchmarks.